Disability Policy and Active Citizenship: The Case of Australia's National Disability Insurance Scheme. (June 2021) - Earle, Timothy; Boucher, Normand
In this article, we illustrate how Australia's new National Disability Insurance Scheme (NDIS) extends the active citizenship of people with disabilities. This is done by examining how the NDIS changes their relation between persons with disabilities and to the welfare state, and through an analysis of its eligibility criteria and needs assessment planning. The support provided and the way in which it is provided reproduce a particular understanding of disability that has a direct influence on the roles assigned to people with disabilities in society as well as on their opportunities to exercise their rights as active citizens. This is important because the implementation of NDIS in Australia is likely to influence the development of disability policy on a global level. Understanding how its mechanisms restricts or facilitates citizenship is therefore crucial.